Fragile alliances in Egypt's post-revolutionary order: The military and its partners - Chérine Chams el- Dine (Stiftung Wissenschaft und Politik (SWP), 2014)
The election of Abdel Fattah al-Sisi in May 2014 as Egypt's President has ushered in a new order. The tacit alliance forged during the rule of Sisi's predecessor, Mohammed Morsi, between the Muslim Brotherhood and the military had gradually eroded by the end of 2012. Currently, the military and the business elites constitute the core of an emerging tactical alliance, with the Salafist Nour party and secular political forces occupying a secondary position. In the mid-term, the consolidation of the post-July 2013 order will depend first and foremost on the alliance's capacity to ensure economic recovery. Secular and Islamist forces have each been forging electoral coalitions to try to win seats in the coming parliamentary elections, which are supposed to take place before the end of 2014. (SWP Comments)
Keywords: 320